Peran Pendidikan dan Pelatihan Terhadap Peningkatan Kinerja Pegawai - Rahman, Ansyari (PREDIKSI, 2016)
Basically, the performance is what employees do so affects how much of their contribution to the institution or organization. One purpose of the implementation of education and training is so that performance can be achieved with the maximum, of the quality of services intended that every employee has the ability to match their respective field of work. Another thing that needs to be examined after education and training is the mastery of technology and improved discipline. Training is one of the important factors in the development of human resources. Training not only gain knowledge, but also improve work skills, thereby increasing productivity. PNS Training is a process of increasing knowledge of education and training is also an activity in improving quality, the development of attitudes and behavior, skills and knowledge of employees. Training Agency established by Regulation (Perda) No. 05 Year 2103 concerning Organization and Work Inspectorate District, before the Regulation No. 05 In 2013 was named Agency for Training and Research, the existence Training Agency started while still Agency and Research Training in mid-year 2009 budget, with funding beginning of the Supplementary Budget. This study focused on data in 2014-2016. Keywords: Board of Education and Training; Performance Improvement; East Kutai Regency===============Pada dasarnya kinerja merupakan apa yang dilakukan pegawai sehingga mempengaruhi seberapa banyak kontribusi mereka kepada instansi atau organisasi.Salah satu tujuan dilaksanakannya pendidikan dan pelatihan adalah agar kinerja dapat tercapai dengan maksimal, dari kualitas pelayanan bertujuan agar setiap pegawai memiliki kemampuan sesuai dengan bidang kerjanya masing-masing. Hal lain yang perlu dicermati setelah melakukan pendidikan dan pelatihan adalah penguasaan teknologi dan peningkatan kedisiplinan.Diklat merupakan salah satu faktor yang penting dalam pengembangan sumber daya manusia. Diklat tidak hanya menambah pengetahuan, akan tetapi juga meningkatkan keterampilan bekerja, dengan demikian meningkatkan produktivitas kerja. Diklat PNS merupakan suatu proses meningkatkan pengetahuan Diklat juga merupakan kegiatan dalam memperbaiki mutu, pengembangan sikap dan tingkah laku, keterampilan dan pengetahuan pegawai.Badan Diklat terbentuk berdasarkan Peraturan Daerah (Perda) No. 05 Tahun 2103 tentang Organisasi dan Tata Kerja Inspektorat Wilayah Kabupaten,sebelumnya adanya Perda No. 05 Tahun 2013 adalah bernama Badan Diklat dan Litbang, eksistensi Badan Diklat dimulai saat masih Badan Diklat dan Litbang pada pertengahan tahun Anggaran 2009 dengan sumber pendanaan awal dari Anggaran Belanja Tambahan. Penelitian ini fokus pada data tahun 2014-2016.Kata Kunci : Badan Pendidikan dan Peltihan; Peningkatan Kinerja; Kabupaten Kutai Timur